International Real Business Cycles - Backus, David K.; Kehoe, Patrick J.; Kydland, Finn E. (Journal of Political Economy, 1992)
The authors ask whether a two-country business cycle model can account simultaneously for domestic and international aspects of business cycles. With this question in mind, the authors document a number of discrepancies between theory and data. The most striking discrepancy concerns the correlations of consumption and output across countries. In this data, outputs are generally more highly correlated across countries than consumptions. In the model they see the opposite. Copyright 1992 by University of Chicago Press.